Three-dimensional human head modelling: a systematic review. (2nd November 2018) - Shah, Parth; Luximon, Yan
ABSTRACT: Human head is one of the most important parts of the body, as it houses brain and other sensory organs, which controls functioning and working of the whole body. The products used for head and face are designed for functions like protection, information transfer, healthcare or to improve the aesthetic appearance. In order for them to serve their purpose, they need a close fit and in order to make it more ergonomic, user's comfort also needs to be addressed, thereby making it necessary to acquire accurate anthropometric data for ergonomic product design. Traditional techniques involve manual measurement using tapes, callipers and scales which normally have low reliability and low accuracy. With the advancement in image processing and computer aided designing and modelling techniques it has become possible to develop highly accurate and reliable 3D head and face model. Following paper presents a systematic review of different approaches that have been proposed for developing 3D head and face model and also the techniques used in processing and analysis of 3D data and their limitations. The paper also presents application of head and face models for ergonomic product design.